Studi Pengaruh Rasio V/III terhadap Morfologi Permukaan Film Tipis GaSb yang - Lilik Hasanah; Euis Sustini; Sukirno Sukirno; Maman Budiman (Institut Teknologi Bandung, 2003)
Gallium Antimony (GaSb) thin film were grown on Semi Insulating (SI) GaAs (100) substrate by MOCVD (Metal-Organic Chemical Vapor Deposition) method. TMGa (trimethylgallium) and TDMASb (tridismethylaminoantimony) were used as precursors of group III and V, respectively, with H2 as gas carrier. The films were grown with V/III varied between 1,15 and 3,1. V/III ratio dependent of surface morphplogy and atomic composition of GaSb thin films were studied. The best surface morphology stoichiometric GaSb obtained at the V/II ratio of 2.0.